Workplace Discrimination and Its Effects on Employees Performance/Productivity: Basis for a Proposed Development Plan: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Discrimination is the act of favoring one group of people over another. When judging ortreating someone based on their demographic traits, such as gender, age, education,employment, marital status, language spoken, and others, it is commonly associated with biasand unfairness. In today's workplaces, discrimination is a sin. In essence, employers have aduty to offer equal employment chances to workers of different genders, colors, ethnicities,and religions, among other personal characteristics. The focus of the entire essay is onworkplace discrimination and how it affects worker productivity. There is no doubt thatprejudice demotivates workers and lowers potential job satisfaction (Denissen & Saguy,2018).The study came up with the results in terms of demographic profile: female employees havethe highest responses and have an age range of 25 and below. The researchers distributedthe questionnaires equally to 10 male and female employees, and most of the respondentswere still single on the assessment of the factors of workplace discrimination that affect theemployees’ performance/productivity in terms of hiring practices, salary gap, and promotion.These variables had the same verbal interpretation of “strongly agree.” There is no significantdifference between the two groups of respondents as to cited variables. Since the t-computedvalue is less than the t-critical value, therefore the null hypothesis of non-significance isaccepted.Based on the findings, the researchers conclude that the majority of the selected respondentsconsider the workplace discrimination that affects the employee’s performance/productivity.Most of the respondents have encountered or experienced workplace discrimination in termsof hiring practices, salary gaps, and promotions. The researcher recommends to theOrganization or Company that they should practice to eliminate workplace discrimination.
Keywords: Business